Conversion of organic fraction of municipal solid waste into solid fuel via hydrothermal carbonization - Eriska Putra, Herlian; Dewi, Kania; Damanhuri, Enri; Darmawan Pasek, Ari (International Journal of Engineering and Technology, 2018)
Hydrothermal carbonization (HTC) is thermochemical process that can convert wet biomass into coal-like material. In this study, a series of HTC experiments was done. In the first stage targeted to obtain the process condition for mixture component. The process conditions comprised temperature, solid load, and holding time. Five typical components were used as representative pseudo-components of organic fraction of municipal solid waste. Each of substrates was carried out on the prototype HTC reactor. Process condition took place temperature at 190, 210 and 230 oC, with a holding time (30 and 60 minutes) and feed to water ratio (0.1, 0,2, 0.3). The result from first stage showed that the optimum process condition for mixture component were temperature 215 oC, 55 minutes, and solid load 0.16. The process conditions were applied for next stage. In the second stage, mixture component comprised 15% fruit peel, 10% food waste, 10% of office paper, 30% leaves, and 35% sawdust were used as feedstock. Model to determine process condition for mixture component and also to predict high heating value have been developed. The fuel characteristics and combustion behavior of HTC-derived hydrochars were evaluated. Hydro-thermal carbonization of waste gave high heating value (HHV) with value of 20.24 MJ/kg higher than its raw 16.42 MJ/kg.